Rasuah dan integriti dalam pentadbiran awam di Malaysia: sorotan literatur / Izawati Wook, Arif Fahmi Md Yusof and Hasnah Haron - Wook, Izawati; Md Yusof, Arif Fahmi; Haron, Hasnah (UiTM Cawangan Kedah, 2022)
Corruption and problems in integrity involving public service in Malaysia are important aspects to be considered, as level of corruption is allegedly regarded as severe in many studies and reports. Corrupt practices in government administration may lead to failures in the delivery system and affects the running functions of an organisation. This paper examines literature on integrity and corruption involving civil servants. It aims to identify the level of risk of corruption involving public administration, factors of corrupt practices, and recommendations to address the issue. This study employs library research by collecting and analysing the related literature. The review of literature finds that the general perception towards corruption is critical. Law enforcement and procurement sectors are found to be detrimental. Low moral and ethical values within the organisation, ineffective law enforcement and inefficient management may lead to opportunity, and risk of corruption. Therefore, education and values of good ethics, are important to ensure a high level of integrity among civil servants in order to reduce the risk of corruption in public administration. This paper also plays a part in identifying the gaps in the literature on integrity and corruption involving public officials and pointing out further aspects for further research.